Are We Deliberately Captivated in Homogeneous Cocoons? An Investigation on Political Tie Building on Facebook. Issue 2 (4th March 2021) - Cargnino, Manuel; Neubaum, German
ABSTRACT: The idea that users of social networking sites (SNS) isolate themselves within like-minded, homogeneous communication environments has been receiving growing scholarly attention. Different from studies on the structure of users' online networks, this work offers initial evidence on the specific behavior of political tie building, i.e., the preferential connection to like-minded SNS users. A pre-registered survey ( N = 469) including German Facebook users shows that political like-mindedness serves as criterion of tie selection only for some. Strength of social identification with a political ingroup is related to higher levels of political tie building which, in turn, is positively (albeit weakly) associated with perceived political homogeneity of Facebook ties. This is one of the first studies to identify the relative importance of politics in the process of tie building in online networks. At the same time, it underscores that SNS platforms such as Facebook are spaces of incidental exposure to cross-cutting political views.